Misi Gereja Melalui Kajian Yohanes 9:1-41 Sebagai Upaya Mengintroduksi Paradigma Terhadap Kaum Disabilitas - William Sesa; Ramli Sarimbangun (Jurnal Teologi Pambelum, 2026)
This study analyzes the narrative of the healing of a man born blind in John 9:1–41, focusing on its implications for the church’s mission in developing an inclusive paradigm toward persons with disabilities. In many religious and social traditions, disability has often been associated with sin or a curse, which has led to stigma and exclusion. In contrast, the Johannine narrative presents Jesus rejecting such assumptions, restoring the man’s sight, and reinstating his dignity as a member of the community. Using a qualitative hermeneutical and narrative-critical approach, supported by literature from biblical commentaries, journals, and books, this paper argues that Jesus’ action was not merely a miraculous healing but also a theological statement that dismantles social stigma, affirms the value of every individual before God, and models a holistic church mission. The study concludes that the contemporary church must move beyond mere charitable aid toward unconditional acceptance, restoration of dignity, and empowerment of persons with disabilities, thereby creating an inclusive and transformative faith community